Cerebellar and brainstem differences in children with developmental coordination disorder: A voxel-based morphometry study - Gill, Kamaldeep K.; Lang, Donna; Zwicker, Jill G. (Frontiers in Human Neuroscience, 2022)
Developmental coordination disorder (DCD) is a neurodevelopmental disorder that significantly impairs a child’s ability to learn motor skills and to perform everyday activities. The cause of DCD is unknown; however, evidence suggests that children with DCD have altered brain structure and function. While the cerebellum has been hypothesized to be involved in developmental coordination disorder, no studies have specifically examined cerebellar structure in this population. The purpose of our study was to examine cerebellar differences in children with DCD compared to typically-developing children. Using voxel-based morphometry, we assessed cerebellar morphology in children 8-12 years of age. Forty-six children (12 typically-developing and 34 with DCD) were investigated using high resolution T1-weighted images, which were then processed using the spatially unbiased atlas template of the cerebellum and brainstem (SUIT) toolbox for a region of interest-based examination of the cerebellum. Results revealed that children with DCD had reduced grey matter volume in several regions, namely: the brainstem, right/left crus I, right crus II, left VI, right VIIb, and right VIIIa lobules. Further, Pearson correlations revealed significant positive associations between the total motor percentile score on the Movement Assessment Battery for Children-2 and regions that had reduced grey matter volume in our cohort (brainstem, left crus I, right VIIb, and right VIIIa). These findings indicate that reductions in cerebellar grey matter volume are associated with poorer motor skills. Given the cerebellum’s involvement in internal models of movement, results of this study may help to explain why children with DCD struggle to learn motor skills.